Amartya Sen: Political Economy in Indonesia (Amartya Sen: The role of politics on the economy in Indonesia) - Mohamad Latief; Alfian Amrullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article will try to uncover the political problems that study specifically the economy in Indonesia using the perspective of Amartya Sen, one of the politicians based on economists from India. Researchers focus on the economic and political phenomena that exist in Indonesia and how the concepts and ideas offered by Sen in alleviating existing problems. This research uses a qualitative method with a descriptive-analytical approach with data obtained and analyzed by researchers and compared with various existing sources including theses, theses and scientific journals that can be trusted. There are various kinds of writings that explain the ideas, ideas or concepts brought by Sen, but no one has discussed specifically how they are implemented in Indonesia. The result of this research is that the ideas offered by Sen can be an alternative in an effort to alleviate the economic crisis and improve the existing political system in Indonesia. The researcher also considers that the ideas he brings are very relevant if applied in this country. Then at the end, it explains how important it is for Indonesian people to be aware and learn from economic and political phenomena in order to achieve a developed Indonesian state and a good economy.